Skillnad mellan versioner av "1.2 Lösning 3a"
Från Mathonline
Taifun (Diskussion | bidrag) m |
Taifun (Diskussion | bidrag) m |
||
Rad 1: | Rad 1: | ||
− | <math> P(x) = | + | <math> P(x) = 4\,x^3 - 2\,x^2\,(2\,x + 6) + 7\,x\,(3 + 2\,x) = </math> |
− | ::<math> = \, | + | ::<math> = \,4\,x^3 -\,4\,x^3\,-\,12\,x^2 +\,21\,x\,+\,14\,x^2 = 2\,x^2 +\,21\,x </math> |
Nuvarande version från 14 april 2011 kl. 13.46
\( P(x) = 4\,x^3 - 2\,x^2\,(2\,x + 6) + 7\,x\,(3 + 2\,x) = \)
- \[ = \,4\,x^3 -\,4\,x^3\,-\,12\,x^2 +\,21\,x\,+\,14\,x^2 = 2\,x^2 +\,21\,x \]